Response to PCV13 vaccination in patients with multiple myeloma versus healthy controls. Issue 2 (1st February 2019) - Mustafa, S. Shahzad; Shah, Deep; Bress, Jonathan; Jamshed, Saad
ABSTRACT: Infections are a major cause of morbidity and mortality in individuals with multiple myeloma (MM). These individuals exhibit humoral dysfunction and show a suboptimal response to pneumococcal polysaccharide vaccine (PPV23). Since pneumococcal conjugate vaccine (PCV13) elicits a T cell dependent response, it is recommended in patients with multiple myeloma. This study compares the initial response to PCV13 and durability of the response at 6 months in patients with multiple myeloma versus normal controls. Seven patients with multiple myeloma and 18 control patients were enrolled in the study. Streptococcal pneumonia serotype IgG titers were drawn at baseline, day 30, and day 180 after MM patients and controls received PCV13. Although vaccination with PCV13 produced a similar initial response in patients with multiple myeloma compared to control subjects, the duration of response may have waned in patients with multiple myeloma as compared to control subjects.